Gestaltning av boendelandskapet i gränsen mellan stad och land - Grendalen, Hanna (2007)
This is a 20 credit Master thesis within the landscape architecture education at the Institute for Landscape Planning at the Swedish University of Agricultural Sciences at Alnarp. Norränga is situated on the fringe of the city of Lund, east of the existing district of Linero.The city planning office of Lund municipality has come up with a "in-depth comprehensive plan" for the exploatation of the eastern area of Lund. The plan concerns an area of 1035 square kilometre which contains at least 1500 nya buildings, two schools, primaryschools, stores and bus station for local bus traffic and the new bus line - Lundalänken. The townplan is inspired from the historical Square block city with defined street system. The municipality has visions of what the green areas should consist of. I have choosen to design some of theese green areas. In the greenstructure ponds and streams with stormwater will be taken care of locally in Norränga and be led to the Råby lake and then further to the recipient of Höje river. The stormwater will enhance the greenstructure. Today, the site is an open agricultural landscape with a slope to the south east and an elevation north of the Dalbyroad. The view is extensive and the vegetation is rare at the site. West of the Arendala farm there is a dens, biologically rich park located, which will connect to the eastern green areas of Norränga. Linero was built in the beginning of the 1970ies. The district consists of miscel-laneous housing areas with green, coherent, but in some places, monotonous green areas. The greenstructure of Norränga will be connected to the existing greenstructure of Linero and paths out in the landscape will be developed to enhance the connection to nature in north east (Kungsmarken) and to the east (Hardeberga, Billebjer, Dalby Norreskog and Söderskog). In the historical square block town the blocks and street open space are easily appreciated and yards and parks well defined rooms. In a dens city the distance shrink, people can meet and people will be less dependent of a car. There will also be room for privacy (garden) semiprivacy (housing yard) and public nature and parks. Different ages use the environment in different ways. To promote everyone's wellbeing and appriciation, a multifunctional enviroment with different levels of scale and details is needed. The built structure of Norränga is well planned but how it relates to the location and existing, adjacent housing area can be discussed. I will come back to this later on in my paper. The greenstructure has been developed and changed through the history, with different prevailing ideal. I think the greenstructure would be more intresting if it would allow to consist of seperate, not always very planned, enviroments, where people can find places and discover paths and short cuts outside the very organized cityenviroment. The stormwater can be a possitve addition in the green structure in the future and different competences have to cooperate to be able to integrate ecology, sustainable developement planning, technology and design.